Metabolomics analysis reveals how water extract of Gastrodia elata helps against heroin addiction - Liang Li; Haijie Cao; Jieyan Li; Haixue Kuang; Zhengzheng Zhou; Qiuhong Wang (Elsevier, 2022)
To investigate the metabolomics changes and potential metabolic mechanisms of water extract of Gastrodia elata (WGE) in the treatment of heroin addicted mice. Sixty male Kunming mice were randomly divided into four groups as control group (n = 10), heroin addicted group (n = 10), natural withdrawal group (n = 10), and GE treatment group (500, 1000, 2000 mg/kg, n = 30). Heroin addicted group were injected subcutaneously in the 13 days with increased dosage from 3 mg/kg to 30 mg/kg. The control group was injected with the same amount of saline in the same manner. After 13 days of heroin administration, the treatment groups were given GE by gavage for a week. The natural withdrawal group was injected with the same amount of saline in the same manner. The metabolites were determined using ultra performance liquid chromatography/tandem mass spectrometry (UPLC-MS/MS). The scatting diagrams were plotted based on orthogonal partial least squares discrimination analysis (OPLS-DA). Potential differential metabolites were obtained using the combination of variable important in projection (VIP) and p value methods. Their metabolic pathways were analyzed using databases such as METLIN, HMDB, KEGG and metaboanalyst 5.0. The GE treatment group (500 mg/kg) could significantly reduce the withdrawal symptoms induced by heroin addiction and significantly improve the weight loss of heroin addicted mice. The metabolomics results showed that GE could regulate the levels of 30 different metabolites in heroin addicted mice, which mainly involved in the metabolism of Glutamic acid, Glutathione and Purine. The water extract of Gastrodia elata in the treatment of heroin addiction was confirmed for the first time in this study. The metabolomics analysis demonstrated that the metabolic disorder of endogenous substances changes from pretreatment to posttreatment. The potential biomarkers of brain damage may be feasible to elucidate its metabolic mechanisms.